Aksesibilitas Petani Terhadap Lembaga Pembiayaan Agribisnis Mangga Gedong Gincu - Fajrin, Nadjwa Aulia; Dinar, Dinar; Sumantri, H.K (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Sidamukti Village is one of the main centers for the cultivation of gedong gincu mangoes in Majalengka Regency. However, recently the mango farmers in the village have faced challenges of limited capital due to the unstable productivity of gedong gincu mangoes. This limitation in capital impacts the use of whatever funds are available in the following season. To address these issues, farmers need to seek alternative financing sources that can optimally support their capital needs. This research aims to find out the capital structure of farmers, the sources and types of agricultural financing, and the accessibility of farmers to financial institutions. The sampling method used in this study is saturated sampling, where all members of the population are used as samples, totaling 30 respondents. The analytical methods used are descriptive analysis and difference test analysis. The research results show that the capital structure of farmers in the Ciandeu Farmers Group consists of self capital comprising 20 respondents or 67%, while 10 respondents or 33% use borrowed capital. The funding sources for farmers in the Ciandeu Farmers Group include KUR Bank BRI, middlemen, and family loans. Farmers' accessibility to financing institutions is quite easy, especially for those borrowing from formal institutions such as banks, due to the existence of unlimited loans, predetermined interest rates, and flexibility in repayment. However, the problem is different for new farmers who experience difficulties in obtaining loans from financial institutions. After analysis using difference tests, there were no significant differences in accessibility among the three financing groups. However, in general, the majority of farmers prefer to go through formal institutions.